Diseño de modulos instruccionales programados y su influencia en el rendimiento académico de los estudiantes de ingeniería química en la asignatura de quimica analítica de la Universidad Nacional de Trujillo - Sabana Gamarra, Roberto Enrique (2008)
The present work investigation respond to the problem: ¿In what measure the aplication the Instruction modules Programed have influence on the student’s academic performance of Analytical Chemistry subject at the National University of Trujillo. This research had as objectives: To elaborate of to process of teaching – learning, for Analytical Chemistry subject, by using technics of the Programmed Instruction to the improvement on the student’s academic performance. The hypothesis proposed: the apply on the Programmed Instruction has significative influence on the student’s academic performance of Analytical Chemistry subject at the National University of Trujillo. For contrasting the hypothesis two groups of students were used: A control group experimental. The experimental group recived the influence of the designed strategy and the control group not, a only strategy in wich teacher activity was predominant, for to the development to every unity the computer was used as an auxiliary device. The inference the statistics was used to analysis the data. Finally it was found that the strategy based on the Programmed has signigicatively inlflyence on the students academic performance of Analytical Chemical of the National University of Trujillo of Analytical Chemistry subject.